2020
DOI: 10.3340/jkns.2020.0128
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Triggering Events on the Occurrence of Spontaneous Intracranial Hemorrhage : Comparison of Non-Lesional Spontaneous Intraparenchymal Hemorrhage and Aneurysmal Subarachnoid Hemorrhage

Abstract: Objective : Spontaneous intracranial hemorrhage is a life-threatening disease, and non-lesional spontaneous intraparenchymal hemorrhage (nIPH) and aneurysmal subarachnoid hemorrhage (aSAH) are the leading causes of spontaneous intracranial hemorrhage. Only a few studies have assessed the association between prior physical activity or triggering events and the occurrence of nIPH or aSAH. The purpose of this study is to investigate the role of specific physical activities and triggering events in the occurrence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…16 Another study in 2020 indicated that aSAH most commonly occurred during nonstrenuous physical activity. 17 From various perspectives, our study reviewed and summarized morbidity characteristics in aSAH patients admitted to Beijing Tiantan Hospital between 2015 and 2020. Our study showed a higher aSAH incidence, advanced age, and smaller mean maximum diameter of the aneurysm in female patients, consistent with previous studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…16 Another study in 2020 indicated that aSAH most commonly occurred during nonstrenuous physical activity. 17 From various perspectives, our study reviewed and summarized morbidity characteristics in aSAH patients admitted to Beijing Tiantan Hospital between 2015 and 2020. Our study showed a higher aSAH incidence, advanced age, and smaller mean maximum diameter of the aneurysm in female patients, consistent with previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…One study in 2007 demonstrated that aneurysmal rupture occurred most frequently when patients were talking, chatting, watching television, or at home without any strenuous physical activity, and hypertension was the most common pre‐existing medical problem 16 . Another study in 2020 indicated that aSAH most commonly occurred during nonstrenuous physical activity 17 . However, highlighting events by patients’ actions may lead to more intuitive recommendations for patients.…”
Section: Discussionmentioning
confidence: 99%